Ultrathin Carbon-Based Overcoats for Extremely High Density Magnetic Recording - Yeo, Reuben Jueyuan (Springer Singapore : Imprint: Springer, 2017)
This book presents the latest research in ultrathin carbon-based protective overcoats for high areal density magnetic data storage systems, with a particular focus on hard disk drives (HDDs) and tape drives. These findings shed new light on how the microstructure and interfacial chemistry of these sub-20 nm overcoats can be engineered at the nanoscale regime to obtain enhanced properties for wear, thermal and corrosion protection - which are critical for such applications. Readers will also be provided with fresh experimental insights into the suitability of graphene as an atomically-thin overcoat for HDD media. The easy readability of this book will appeal to a wide audience, ranging from non-specialists with a general interest in the field to scientists and industry professionals directly involved in thin film and coatings research.
Keywords: Materials science.; Magnetism.; Magnetic materials.; Engineering -- Materials.; Materials -- Surfaces.; Thin films.; elektronické knihy; electronic books